Analysis of the Application of Accounting Information Systems for Cash Receipts and Disbursements in Hospitals: Literature Review - Amnatia R Abdullah (Westscience Press, 2024)
The crucial role of hospitals in health care and the need for professional management as well as the emphasis on advances in information technology and the urgency of accounting information systems were identified. The purpose of this research is to evaluate literature studies to determine the application of accounting information systems for cash receipts and disbursements in various hospitals. The research method used a literature review of several national articles that were searched using google scholar set aside 10 articles with the keywords hospital cash receipts and disbursements. The review results from 10 articles showed a variety of impacts and benefits, including implementation challenges in some hospitals. Findings included technological constraints, calculation errors, and potential operational efficiencies. Nonetheless, certain hospitals managed to implement accounting information systems well, minimize the risk of errors, and improve efficiency. Conclusion: Accounting information system implementation contributes to operational efficiency, internal control, and financial statement accuracy, with a focus on resource optimization and reputation enhancement. Continuous efforts and technology integration are the keys to optimal system implementation in hospitals.